Estimation of direct normal irradiance under various sky condi-tions in data sparse tropical ecological zones in Nigeria - Nwokolo, Samuel; Ogbulezie, Julie (International Journal of Advanced Astronomy, 2017)
In this study, models for estimating direct normal irradiance (Hb) under various sky conditions in data sparse tropical ecological zones in Nigeria were fitted. The evaluated values of clearness index indicate that the prevailing sky condition in the southern tropical zones is heavily overcast while the northern zones experience partly overcast under all sky conditions. From the analyses of the influences of clearness index on Hb, it was observed that higher values of Hb were recorded in the far north zone of Sahel savannah (FNZSS) of Sokoto while lower values were registered in the far south zone of mangrove swamp of Port Harcourt revealing an increasing trend from FSZMS to FNZSS due to the trends in cloudiness and associated atmospheric moisture with the movement through the Hadley cell calculation system along the equatorial line. The regression correlation models developed from the model performance test indicates that the proposed models could be used to estimate Hb accurately between latitude 4 to 10oN, that is, mangroves swamp and Guinea savannah tropical zones in Nigeria and other locations with comparable sky conditions.